WebTrackingScore: A Combined Web Tracking Risk Score System for Websites - Álvaro D. Guillén Cava; Antonio Ruiz-Martínez (Future Internet)
Privacy awareness has increased in recent years. In many countries, websites warn users about their use of cookies and Web browsers provide mechanisms to protect user privacy. However, it is not easy for users to understand tracking risks associated with browsing a given website. To address this, several privacy scanners have emerged to evaluate the privacy practices of websites. However, the scores these scanners provide are often limited to a small number of Web tracking indicators and are thus incomplete. To overcome this limitation, in this paper, we present WebTrackingScore, which provides users with a simple and intuitive indication of the privacy risk associated with visiting a website from a tracking perspective. Its design is based on an in-depth analysis of tracking mechanisms and the behaviour of some of the most frequently visited sites. Based on WebTrackingScore, we have analysed how the most popular websites are classified.